From Certification to Practice: How We Implement Positive Discipline in Our Nursery Schools (Journal of Parents and Teachers, 2023)
Based on the belief that each child is special and unique and with the desire to take care of their happiness and development in the first years of life (0-3), this article describes the experience of the implementation process of the Discipline. Positive as an educational model in the nursery schools of El Mundo de Mozart.
Keywords: positive discipline; children's school; educate positive; early childhood; implementation